Capabilities dan Functionings Rohaniwan Hindu (Sulinggih) di Bali - Anak Agung Ketut Ayuningsasi; I Wayan Sukadana; Ni Putu Ganish Sanjiwani; Ni Luh Putu Setia Rahini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research aims to explore the concept of capabilities and functionings according to Hindu clergy (Sulinggih) in Bali, and then identify and confirm the dimensions. These two terms make an important contribution to Amartya Sen's theory of well-being, and this research develops these two concepts in the clergy. This research was designed using mixed methods (exploratory sequential mixed methods) through qualitative research with in-depth interviews with 10 informants and carrying out FGDs attended by 12 participants to explore the concept of Sulinggih's capabilities and functioning and identify its constituent dimensions. The data was analyzed using the Miles and Huberman model using the NVivo application for the data reduction process. The results of the concept analysis and forming dimensions were then confirmed quantitatively with confirmatory factor analysis (CFA) through data collected from questionnaires to 95 respondents. The findings in this research are that functioning in clergy life also involves various aspects of life (not only spiritual aspects), including material, physical, psychological, and social aspects. Capabilities, according to clergy in Bali, are capabilities for the health of the body, thoughts, feelings, and affiliation. The contribution of this research in developing the concept of well-being of the clergy and the implications of this research in religious life in Bali are also discussed in this paper.